PENGARUH COMPANY SIZE, LEVERAGE, DAN FAKTOR LAIN TERHADAP TAX AVOIDANCE - Bernardi, Lianita; Yohanes (E-Jurnal Akuntansi TSM, 2023)
The purpose of this research is to obtain empirical evidence regarding the effect of earnings management, independent commissioner, audit committee, institutional ownership, board of commissioners activities, company size and leverage on tax avoidance. This study uses the data population used in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2021 period. Sample selection uses the purposive sampling method with a total of 207 companies and a total sample data of 69 companies. This study used the method of multiple regression data analysis. The results of this study indicate that leverage has an effect on tax avoidance meanwile earnings management, independent commissioners, audit committee, institutional ownership, board of commissioners activities and company size have no influence on tax avoidance. The higher the leverage or debt of the company, the higher the tax burden will be, so that the company does not tend to do tax avoidance. Companies that use debt to finance large amounts of operational costs will have a high tax burden so that companies tend not to do tax avoidance.